Improving the practice of identifying socially vulnerable segments of the population: world experience and national characteristics - ugli, Bakhtiyorov Bobur Bakhodir (International Journal of Psychosocial Rehabilitation, 2020)
This article investigates improving the practice of identifying socially vulnerable segments of the population: world experience and national characteristics. Moreover, research has been analyzed both methodology and theoretically while focusing on the different points as the whole. In conclusion, outcomes and shortcomings of the identifying socially vulnerable segments of the population in case of world experience and national characteristics pointed out with the vivid examples.